The Role of Organizational Culture in Improving the Performance of Human Resources in Higher Education - Yulianto (Technium Social Sciences Journal, 2020)
An organizational culture development will be successful if it is accompanied by efforts to optimize positive behavior and minimize negative behavior. For this reason, it is necessary to reform the organizational culture in universities. An organizational culture in a university will provide a set of norms needed by members of the organization, so that it can provide a strong meaning to what the human resources in the university are doing. The purpose of this study was to find answers on how organizational culture is applied in a higher education institution and what factors drive the improvement of the human resources performance in higher education. This research applies a case study approach from qualitative research design. In this study a semi-structured interview is used to get the perspectives of the employees of organizational culture and performance. The research proved that an organizational culture that is well socialized to the entire academic community will provide a thorough understanding to each employee so that it can be applied in daily activities and the improvement of performance quality can be increased by creating good work environment, training, motivation, reward and coercive. clear job descriptions and periodical job evaluations.